Groin injecting among a community-recruited sample of people who inject drugs in Thailand - Ti, Lianping (BioMed Central, 2014)
BACKGROUND: Use of the femoral vein for the injection of illicit drugs (i.e. groin injecting) has been linked to various health-related harms, including deep vein thrombosis. However, little is known about the prevalence of groin injecting and factors that predict this practice among people who inject drugs (PWID) in Thailand. We sought to investigate the prevalence and factors associated with groin injecting in Bangkok, Thailand. METHODS: Data were derived from the Mitsampan Community Research Project in Bangkok between July and October 2011. Multivariate logistic regression was used to identify factors associated with groin injecting in the last six months. RESULTS: Among 437 participants, 34.3% reported groin injecting in the last six months. In multivariate analyses, factors positively associated with groin injecting included: having higher than secondary education (adjusted odds ratio [AOR] = 1.59; 95% confidence interval [CI]: 1.00 – 2.56), weekly midazolam injection (AOR = 8.26; 95% CI: 5.04 – 14.06), and reports of having had drugs planted on oneself by police (AOR = 2.14; 95% CI: 1.37 – 3.36). CONCLUSIONS: Over one-third of our sample of Thai PWID reported recent groin injecting. Frequent midazolam injection and higher education were found to be associated with groin injecting. That high intensity PWID were more likely to inject in the groin is concerning given the known negative consequences associated with the groin as a site of injection. Additionally, PWID who reported drug planting by police were more likely to inject in the groin, suggesting that reliance on law enforcement approaches may undermine safe injection practices in this setting. These findings highlight the need for evidence-based interventions to address the harms associated with groin injecting, including efforts to alert PWID to risks of groin injecting, the distribution of appropriate injecting equipment, and efforts to encourage use of other injecting sites.